Spatial Analysis of Population Distribution and Urban Services in Anzali City Based on the TOPSIS Model - Mohammad Eskandari Nodeh; Mozhgan Khoshdelan (جغرافیا و پایداری محیط)
The purpose of this study is to evaluate the coordination of population and urban service distribution in Anzali city, and try to provide a planned strategy to balance the distributtion os services in the whole city, so that all the citizens could benefit from these facilities. The research method is descriptive and analytical method where we use coefficient entropy and Gini method to analyze the population distribution and the TOPSIS model for analyzing urban service distribution. The Research Population is 9Anzali's urban areas specified based on the city's comprehensive plan which have been evaluated by 8 utilities Indexes. Results of the study show that the distribution of population in urban areas is balanced, but only 13 percent of the total population of the city utilize balanced urban service and 40% of the population located in semi-balanced situation and 47 percent located in unbalanced terms of urban services. applying Pearson’s correlation between the demographics and distribution of urban services in urban areas, indicates a lack of correlation between the two mrntioned variables.Thus, in addition to a need for increasing the quality of urban ​​service parameters, establishing an effective communication and coordination between the population and urban service distribution in the areas of Bandar Anzali is necessary.